DETERMINAN LOYALITAS KONSUMEN STARBUCKS MEDAN DARI FAKTOR KEPUASAN KONSUMEN, CITA RASA DAN CUSTOMER EXPERIENCE DI APLIKASI STARBUCKS REWARDS - Feriani Astuti Tarigan; Irwadi Irwadi (Bisnis-Net, 2026)
The growing coffee culture in Medan has intensified competition among coffee shops, including Starbucks, which is currently experiencing a decline in customer loyalty as reflected in decreasing sales and fewer customer visits. A preliminary survey indicates dissatisfaction with pricing and service, inconsistent taste quality, and a less-than-optimal experience with the Starbucks Rewards application, all of which have weakened customer attachment. The study targeted all Starbucks consumers, with an unknown population size; therefore, the Lemeshow formula was used to determine the sample size as much as 100 respondents, and accidental sampling was applied. The findings conclude that customer satisfaction, product taste, and customer experience through the Starbucks Rewards application, both partially and simultaneously, have a significant influence on customer loyalty at Starbucks in Medan.